Classical apologetics a rational defense of the Christian faith and a critique of presuppositional apologetics - Sproul, Robert Charles, 1939-; Gerstner, John H.; Lindsley, Arthur (Grand Rapids, MI Zondervan, 1985)
Includes bibliographical references and index.
Keywords: Apologetics; Natural theology